Role of Inflammation in Coronary Epicardial and Microvascular Dysfunction - Shigeo Godo (Radcliffe Medical Media, 2021)
There is accumulating evidence highlighting a close relationship between inflammation and coronary microvascular dysfunction (CMD) in various experimental and clinical settings, with major clinical implications. Chronic low-grade vascular inflammation plays important roles in the underlying mechanisms behind CMD, especially in patients with coronary artery disease, obesity, heart failure with preserved ejection fraction and chronic inflammatory rheumatoid diseases. The central mechanisms of coronary vasomotion abnormalities comprise enhanced coronary vasoconstrictor reactivity, reduced endothelium-dependent and -independent coronary vasodilator capacity and increased coronary microvascular resistance, where inflammatory mediators and responses are substantially involved. How to modulate CMD to improve clinical outcomes of patients with the disorder and whether CMD management by targeting inflammatory responses can benefit patients remain challenging questions in need of further research. This review provides a concise overview of the current knowledge of the involvement of inflammation in the pathophysiology and molecular mechanisms of CMD from bench to bedside.